Nostalgia for the Closet: Tender Connections in Contemporary American Adolescent Literature - (:unkn) unknown (My University, 2025)
This dissertation examines the tenderness and nostalgia for the closet in contemporary American adolescent literature. I build a focused timeline from approximately 2010 to 2023, selecting mainstream American texts aimed towards adolescent readers and explore the depiction of the closet throughout. For each text I explore, I analyze a moment in queer history that coincides with the time of publication in order to demonstrate the influence of that context, as well as connect the analysis to the larger intracommunity conversation between queer adults and queer adolescents. Tenderness and connection are a common thread throughout these texts, emerging from the relationship between affect, privacy, and capitalism as they connect to contemporary concerns. I argue that the nostalgia for the closet that I find throughout these texts are connected to their particular moments, and that this timeline illustrates how desires for privacy and normalcy result in the closet being depicted as a space of safety and connection rather than a space of shame or confinement.
Keywords: American literature; LGBTQ studies; Literature; Adolescent literature; Affect theory; American literature; Contemporary literature; Queer literature; Queer theory